Habit or Utility: A Key Choice Point in Promoting the Adoption of Telehealth in China. (4th July 2020) - Fan, Yun; Liu, Sifeng; Liu, Jun; Javed, Saad Ahmed; Fang, Zhigeng
Abstract : Telehealth, as an indispensable means of technical support in the Healthy China Strategy, currently has less than 20 percent adoption rate in China despite a great deal of government policies and investments. In the current study, to analyse the influencing factors behind doctors' and patients' adoption of telehealth, an asymmetric dynamic evolutionary game model of doctor-patient behaviour selection was established. Based on the model solution, the evolutionarily stable strategies that emerge in different situations were analysed. The results show that it is difficult for the adoption of telehealth in China to keep pace with coverage due to the "dual low" nature of telehealth: both doctors' utility from telehealth and patients' telehealth cost threshold are too low to incentivize adoption. The strategy to promote the adoption of telehealth in China should include providing adequate training for doctors and patients on the use of telehealth technology, rewarding doctors who provide telehealth services and raising the threshold cost of patient's telehealth adoption.